2017
DOI: 10.1007/s00330-017-4846-4
|View full text |Cite
|
Sign up to set email alerts
|

Capsule, septum, and T2 hyperintense foci for differentiation between large hepatocellular carcinoma (≥5 cm) and intrahepatic cholangiocarcinoma on gadoxetic acid MRI

Abstract: • Capsule, septum, and T2 hyperintense foci were useful for characterizing large HCC. • Adding ancillary features to enhancement pattern increased accuracy for diagnosing large HCC. • Interobserver agreement was substantial to excellent for ancillary features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Reviewers were blinded to clinical details, pathological results, as well as DWI findings. Diagnoses were made using the following five‐point scale (see Supplementary Material) : 1, probably HCC (S1); 2, possibly HCC (S2); 3, indeterminate (S3); 4, possibly IMCC (S4); and 5, probably IMCC (S5). Categories can be adjusted according to the presence of some imaging features in T 1 WI and T 2 WI.…”
Section: Methodsmentioning
confidence: 99%
“…Reviewers were blinded to clinical details, pathological results, as well as DWI findings. Diagnoses were made using the following five‐point scale (see Supplementary Material) : 1, probably HCC (S1); 2, possibly HCC (S2); 3, indeterminate (S3); 4, possibly IMCC (S4); and 5, probably IMCC (S5). Categories can be adjusted according to the presence of some imaging features in T 1 WI and T 2 WI.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, central ischemia or necrosis in biologically aggressive tumors such as poorly differentiated HCCs or sarcomatoid HCCs may also result in the targetoid appearance (394041). In addition, large HCCs (≥ 5 cm) also frequently show the targetoid appearance on imaging studies due to heterogeneous internal contents, including necrotic content (4243).…”
Section: Hccs With Atypical Imaging Featuresmentioning
confidence: 99%
“…In a similar vein, large HCCs (≥ 5 cm) often show relatively large amount of necrosis and hemorrhage in their internal contents. Consequently, large HCCs could show LR-M (probably or definitely malignant but not HCC specific) features such as peripheral enhancement with centripetal fill-in on CT or MRI (4243). Hwang et al (43) demonstrated that capsule, septum, and T2 hyperintense foci were more frequently observed in large HCCs than in ICCs on gadoxetic acid-enhanced MRI.…”
Section: Hccs With Atypical Imaging Featuresmentioning
confidence: 99%
See 2 more Smart Citations